Tax and not Tax on Capital Structure of Real Estate and Property Company - Thalib, Fauzi; Herdiyana, Herdiyana; Wahid, Ayi (International Journal of Economics and Financial Issues, 2019)
This study aims to examine and analyze the effect of corporate tax rate, non-debt tax shield, investment opportunity set, profitability, and sales growth to the level of debt (leverage) on real estate and property companies listed on Indonesia Stock Exchange Period 2011-2015. This study uses panel data regression with fixed effect model to estimate 40 companies selected through purposive sampling. The results showed that corporate tax rate, non-debt tax shield, investment opportunity set, profitability, and sales growth have a significant effect simultaneously on debt level. Partially, from the five independent variables are known there are three variables that significantly affect the leverage of corporate tax rate, investment opportunity set, profitability, while the other two variables namely Non-debt Tax Shield and Sales Growth have no significant effect. This shows that Non-debt Tax Shield and Sales Growth statistically does not affect the level of debt in the real estate and property companies listed on the Indonesia Stock Exchange. Keywords: Tax, Shield, Profitability, Leverage, Property. JEL Classifications: E10, E32, E60 DOI: https://doi.org/10.32479/ijefi.7613